Construction of Ag‐Bridged Z‐Scheme LaFe0.5Co0.5O3/Ag10/Graphitic Carbon Nitride Heterojunctions for Photo‐Fenton Degradation of Tetracycline Hydrochloride: Interfacial Electron Effect and Reaction Mechanism. Issue 5 (15th January 2022) - Xu, Xuelian; Lin, Hao; Xiao, Ping; Zhu, Junjiang; Bi, Huiting; Carabineiro, Sónia A. C.
Abstract: Improvements on spectral absorption range and electron–hole (e − /h + ) separation efficiency are crucial to effectively design materials for photocatalysis. To reach this objective, ternary Z‐scheme LaFe0.5 Co0.5 O3 /Ag10 /graphitic carbon nitride (LFCO/Ag10 /g‐CN) heterojunctions with layered structure are designed. The obtained results show that: 1) the Ag nanoparticles (NPs) act as bridges to link LFCO and g‐CN, providing a place for recombination of useless electrons and holes; 2) some of the Ag atoms enter the LFCO lattice as Ag +, but most of them are at the surface in the form of Ag NPs, while g‐CN coats the surface of LFCO/Ag10 as a thin film; 3) LFCO/Ag10 /g‐CN exhibits improved e − /h + separation efficiency, electron transfer rate, and photocurrent response, compared to g‐CN and LFCO/Ag10 alone. Catalytic tests show that LFCO/Ag10 /g‐CN is active for photo‐Fenton degradation of tetracycline hydrochloride (TC), with 87% TC conversion obtained at 40 min. Mechanistic studies show that O 2− and OH radicals are the reactive species of the reaction, and a synergistic effect between light and H2 O2 is produced by generating extra OH radicals. LFCO/Ag10 /g‐CN is also highly stable in the reaction conditions, with no appreciable activity loss up to four reuse cycles. Abstract : Ternary Z‐scheme LaFe0.5 Co0.5 O3 /Ag10 /graphitic carbon nitride heterojunctions (LFCO/Ag10 /g‐CN) with layered structure are prepared and used as catalysts for photo‐Fenton degradation of tetracycline hydrochloride. The materials show enhanced activity for the reaction due to synergistic effects induced between LFCO and g‐CN, and between light and H2 O2 . A mechanism containing three reaction steps is proposed.